Preparation method of high-strength and high-density graphite
Patent Information
- Application Number
- CN202511471968.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-15
AI Technical Summary
[0006]本发明的目的在于提供一种高强高密石墨的制备方法,以解决现有技术中石墨制备焙烧沥青结焦值低,需要反复浸渍和焙烧的问题
[0019] 1. This innovative method for preparing high-strength, high-density graphite involves uniformly coating carbon graphite products after a single calcination and impregnation with a mixture containing volatiles using isostatic pressing. During calcination, the light asphalt components inside the product are heated and volatilized, making them difficult to expel at the interface between the product and the coating layer. This creates positive pressure at the interface, inhibiting the volatilization of the light asphalt components inside the product, significantly increasing its coking value, and thus greatly improving the product's density and strength. It is particularly suitable for large-scale molded or isostatically pressed products. The process is simple and can achieve a single impregnation, replacing the two or even three impregnations required in industry, facilitating industrial production.
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphite preparation technology, specifically a method for preparing high-strength, high-density graphite. Background Technology
[0002] Currently, the domestic method for preparing graphite materials using asphalt as a binder and coke as aggregate still follows the process of grinding, kneading, secondary grinding, molding, firing, impregnation, and graphitization. This process suffers from drawbacks such as long preparation cycles, cumbersome methods, and high energy consumption. The repeated impregnation and firing cycles account for approximately one-third of the entire process. The main reason is that the asphalt in the green body contains a significant amount of lightweight components that volatilize during firing, creating numerous micropores and other defects, resulting in minimal density increase after firing. Therefore, to achieve high density and high strength, repeated impregnation and firing of the carbon-graphite material samples are necessary to improve density and strength, but this comes at the cost of cost and time.
[0003] Industrially, the main calcination equipment for carbon graphite production is the ring calciner and a small number of rotary kilns, all of which operate under atmospheric pressure. The coking value of the products after calcination is very low, especially the coking value of the re-calcined pitch after impregnation, which is less than 40%. Therefore, the increase in density and strength after each impregnation and calcination is limited. The coking value index is equivalent to the coking residual carbon rate, that is, the proportion of fixed carbon in the pitch that remains as structural strength after calcination. For a product impregnated in a single calcination, its coking value = (weight of the second calcined product - weight of the first calcined product) / total weight of the impregnated pitch impregnated in the first calcined product * 100%, where the difference in weight between the second and first calcined products represents the weight of the impregnated pitch that remains after the second calcination.
[0004] To improve the coking value during roasting, a pressure roasting method has been adopted. For example, in the invention patent with publication number CN102249212A entitled "Pressure Roasting Method for Carbon," the main steps are: 1) placing the pressed green product in a sagger, with filler material added between the product and the sagger; 2) sealing the sagger after loading the product, evacuating it, and then filling it with nitrogen; 3) placing the sagger in a roasting furnace, heating it, and adjusting the pressure inside the sagger to maintain it at 2.5–1.5 MPa. When the pressure exceeds the upper limit, it can be released through a valve, and the valve is closed when it approaches the lower limit. This invention is equivalent to placing the green product in a sagger for pressure roasting in a single roasting process, which can effectively improve the coking value and thus increase density and strength. However, the conditions are quite demanding, requiring good sagger sealing and pressure, which significantly increases costs and makes it difficult to promote large-scale industrial application.
[0005] In summary, there is an urgent need for a method to prepare high-strength, high-density graphite to solve the above problems. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing high-strength, high-density graphite, in order to solve the problem in the prior art that the coking value of graphite in the preparation of calcined pitch is low and that repeated impregnation and calcination are required.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing high-strength, high-density graphite, comprising the following:
[0008] 1) Matrix preparation: The carbon graphite after one firing and impregnation is used as the matrix, and the carbon graphite matrix green body is formed by isostatic pressing.
[0009] 2) Mixture preparation: The mixture consists of at least three of the following: yellow sand, metallurgical coke, coke powder, raw coke powder, and paste powder. The mixture must contain at least one of the following: raw coke powder or paste powder. The paste powder is a mixture of coke powder and asphalt, with the asphalt content ranging from 5% to 40% by mass. The volatile matter content of the mixture ranges from 4% to 13% by mass.
[0010] 3) Molding and wrapping of the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, so that the carbon graphite substrate is completely wrapped by the mixed material. Seal the rubber sleeve, and after vacuuming, perform isostatic pressing. The maximum pressure of isostatic pressing should be less than the molding pressure of the carbon graphite substrate green body.
[0011] 4) Subsequent process: The encapsulated matrix obtained in step 3) is loaded into a furnace and roasted in a ring furnace for 300-480 hours, and then graphitized to obtain high-strength and high-density graphite.
[0012] Preferably, in step 3) above, the thickness of the coating layer formed by the mixture on the surface of the carbon graphite matrix is 0.2-2 times the corresponding dimension of the carbon graphite matrix.
[0013] Preferably, in step 2) above, the D50 of the particle size of yellow sand and metallurgical coke particles is 0.5-5mm, and the D50 of the particle size of coke powder, raw coke powder and paste powder is 5-500μm.
[0014] Preferably, in step 3) above, the vacuuming time is 3-10 hours.
[0015] Preferably, in step 3) above, the pressure for isostatic pressing after vacuuming is 20-130 MPa.
[0016] Preferably, in step 1) above, the particle size D50 of the carbon graphite matrix green body is 0.5-5000 μm, and its shape is cuboid or cylindrical.
[0017] Preferably, in step 4) above, the calcination temperature is 800-1200℃; the graphitization temperature is 2500-2900℃, and the holding time is 6-24h.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. This innovative method for preparing high-strength, high-density graphite involves uniformly coating carbon graphite products after a single calcination and impregnation with a mixture containing volatiles using isostatic pressing. During calcination, the light asphalt components inside the product are heated and volatilized, making them difficult to expel at the interface between the product and the coating layer. This creates positive pressure at the interface, inhibiting the volatilization of the light asphalt components inside the product, significantly increasing its coking value, and thus greatly improving the product's density and strength. It is particularly suitable for large-scale molded or isostatically pressed products. The process is simple and can achieve a single impregnation, replacing the two or even three impregnations required in industry, facilitating industrial production.
[0020] 2. The preparation method of this high-strength and high-density graphite contains 4-13% volatile matter in the mixture. During calcination, a small number of micropores will also appear in the mixture, which can prevent excessive pressure at the interface from causing furnace explosion. Detailed Implementation
[0021] This invention uses a mixture to coat a carbon-graphite matrix that has undergone one-time baking and impregnation. During the second baking, the matrix can be baked under positive pressure under normal pressure in a furnace. By controlling the particle size and composition of the mixture, the internal pressure of the matrix can be controlled, thereby significantly increasing the coking value of the impregnated asphalt and thus substantially improving the strength and density of the product. Specifically, it includes the following steps:
[0022] 1) Matrix preparation: The carbon graphite after one calcination and impregnation is used as the matrix. The carbon graphite matrix green body is formed by isostatic pressing. The composition can be ultrafine, fine, medium-coarse or coarse graphite. Optionally, the particle size D50 of the carbon graphite matrix green body formulation is 0.5-5000μm, and its shape is preferably cuboid or cylindrical. Large-size isostatic pressing is preferred.
[0023] 2) Mixture preparation: The mixture consists of at least three of the following: yellow sand, metallurgical coke, coke powder, raw coke powder, and paste powder. The mixture must contain at least one of the following: raw coke powder or paste powder. The paste powder is a mixture of coke powder and asphalt, with the asphalt content ranging from 5% to 40% by mass. The volatile matter content of the mixture ranges from 4% to 13% by mass.
[0024] In a preferred embodiment, the D50 of the yellow sand and metallurgical coke particles is 0.5-5 mm, and the D50 of the coke powder, raw coke powder and paste powder is 5-500 μm.
[0025] 3) Molding and wrapping the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) to the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, so that the carbon graphite substrate is completely wrapped by the mixed material. Seal the rubber sleeve, and after vacuuming, perform isostatic pressing. The maximum pressure of isostatic pressing should be less than the molding pressure of the carbon graphite substrate green body (the molding pressure of the carbon graphite substrate green body should be at least 30 MPa).
[0026] In a preferred embodiment, the thickness of the coating layer formed by the mixture on the surface of the carbon-graphite matrix is 0.2-2 times the corresponding dimension of the carbon-graphite matrix; for reference, for a cuboid matrix, the corresponding directions are the length, width and thickness, and for a cylindrical matrix, the main directions are the axial direction and the radial direction, corresponding to the height and diameter of the cylinder, respectively.
[0027] Optionally, the vacuuming time is 3-10 hours; the pressure for isostatic pressing after vacuuming can be 20-130 MPa.
[0028] 4) Subsequent process: The encapsulated matrix obtained in step 3) is loaded into the furnace and roasted in a ring roasting furnace for 300-480 hours, and then graphitized to obtain high-strength and high-density graphite. For reference, the roasting temperature can be 800-1200℃; the graphitization temperature can be 2500-2900℃, and the temperature can be maintained for 6-24 hours.
[0029] The present invention will be further illustrated by several embodiments below.
[0030] Example 1
[0031] 1) Matrix preparation: The isostatically pressed carbon graphite after one calcination and impregnation is used as the matrix, with a size of 1200mm*800mm*500mm, and the particle size D50 of the formulation is 8μm, and its shape is cuboid.
[0032] 2) Mixture preparation: The mixture is composed of yellow sand, coke powder, raw coke powder and paste powder, and is uniformly mixed. The particle size D50 of the yellow sand is 3mm, and the particle size D50 of the coke powder, raw coke powder and paste powder is 20μm. The volatile matter content of the mixture is 8%.
[0033] 3) Molding and wrapping of the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, seal the rubber sleeve, vacuum for 7 hours, and perform isostatic pressing at a pressure of 100MPa. The thickness of the wrapping layer formed by the mixed material is 1 times its corresponding dimension. For a cuboid substrate, the corresponding dimensions are the length, width, and thickness.
[0034] 4) Subsequent process: The encapsulated matrix obtained in step 4) is loaded into a furnace and roasted in a ring furnace for 390 hours, and then graphitized to obtain high-strength and high-density graphite.
[0035] Example 2
[0036] 1) Matrix preparation: The isostatically pressed carbon graphite after one calcination and impregnation is used as the matrix, with a size of φ800*1000mm, a particle size D50 of 2500μm, and a cylindrical shape.
[0037] 2) Mixture preparation: The mixture is composed of metallurgical coke, coke powder, raw coke powder and paste powder, and is uniformly mixed. The D50 of the metallurgical coke particles is 5mm, and the D50 of the coke powder, raw coke powder and paste powder is 500μm. The volatile matter content of the mixture is 13%.
[0038] 3) Molding and wrapping of the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, seal the rubber sleeve, vacuum for 10 hours, and perform isostatic pressing at a pressure of 20MPa. The thickness of the wrapping layer formed by the mixed material is twice the dimension in its corresponding direction. The cylindrical substrate mainly corresponds to the height and diameter of the cylinder in the axial and radial directions, respectively.
[0039] 4) Subsequent process: The encapsulated matrix obtained in step 4) is loaded into a furnace and roasted in a ring furnace for 300 hours, and then graphitized to obtain high-strength and high-density graphite.
[0040] Example 3
[0041] 1) Matrix preparation: The isostatically pressed carbon graphite after one calcination and impregnation is used as the matrix, with a size of 1000mm*400mm*400mm, a particle size D50 of 0.5μm, and a cuboid shape.
[0042] 2) Mixture preparation: The mixture is composed of yellow sand, metallurgical coke, coke powder, raw coke powder and paste powder, and is uniformly mixed. The particle size D50 of yellow sand and metallurgical coke is 0.5mm, the particle size D50 of coke powder, raw coke powder and paste powder is 5μm, and the volatile matter content of the mixture is 4%.
[0043] 3) Molding and wrapping of the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, seal the rubber sleeve, vacuum for 3 hours, and perform isostatic pressing at a pressure of 80 MPa. The thickness of the wrapping layer formed by the mixed material is 0.2 times its corresponding dimension. For a cuboid substrate, the corresponding dimensions are the length, width, and thickness.
[0044] 4) Subsequent process: The encapsulated matrix obtained in step 4) is loaded into a furnace and roasted in a ring furnace for 480 hours, and then graphitized to obtain high-strength and high-density graphite.
[0045] Example 4
[0046] 1) Matrix preparation: The matrix is isostatically pressed carbon graphite after one calcination and impregnation, with a size of 1200mm*800mm*500mm, a particle size D50 of 200μm, and a cuboid shape.
[0047] 2) Mixture preparation: The mixture is composed of yellow sand, coke powder, raw coke powder and paste powder, and is uniformly mixed. The particle size D50 of the yellow sand is 1mm, and the particle size D50 of the coke powder, raw coke powder and paste powder is 50μm. The volatile matter content of the mixture is 10%.
[0048] 3) Molding and wrapping of the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, seal the rubber sleeve, vacuum for 10 hours, and perform isostatic pressing at a pressure of 100MPa. The thickness of the wrapping layer formed by the mixed material is 1 times its corresponding dimension. For a cuboid substrate, the corresponding dimensions are the length, width, and thickness.
[0049] 4) Subsequent process: The encapsulated matrix obtained in step 4) is loaded into a furnace and roasted in a ring furnace for 400 hours, and then graphitized to obtain high-strength and high-density graphite.
[0050] Comparative Example 1
[0051] The isostatically pressed carbon graphite (1200mm*800mm*500mm in size, with a particle size D50 of 8μm) after one calcination and impregnation in Example 1 was directly calcined in a ring furnace without coating the mixture for 390 hours, and then graphitized to obtain high-strength and high-density graphite.
[0052] Comparative Example 2
[0053] The isostatically pressed carbon graphite (1200mm*800mm*500mm in size, with a particle size D50 of 8μm) after one calcination and impregnation in Example 1 was directly calcined in a high-pressure calcination furnace without coating the mixture. The pressure was 1.5MPa and the calcination time was 390h. Then, graphitization was carried out to obtain high-strength and high-density graphite.
[0054] Table 1 Performance indicators of the examples and comparative products
[0055] Secondary roasting coking value / % <![CDATA[Bulk density of graphite / g / cm 3 > Graphite flexural strength / MPa Example 1 80.3 1.90 71 Example 2 77.2 1.86 29 Example 3 82.1 1.92 78 Example 4 79.6 1.88 41 Comparative Example 1 37.8 1.85 55 Comparative Example 2 60.1 1.87 62
[0056] Table 1 compares the performance of four examples and two comparative examples. The table shows that, using the encapsulation method of this invention, Example 1 exhibits significantly higher coking values, bulk density, and flexural strength in its final graphite product compared to Comparative Examples 1 and 2. This is primarily because Comparative Example 1 utilizes conventional industrial production methods, employing atmospheric pressure for secondary roasting. During this process, a large amount of light and medium components in the asphalt are volatilized, resulting in a very low coking value. Comparative Example 2, based on Comparative Example 1, uses high-pressure roasting, leading to a significant increase in coking value, but it remains lower than Example 1. This is mainly due to the increased volume of melted asphalt during heating in Comparative Example 2, resulting in more asphalt flowing into the looser filler. Furthermore, Example 1 also experiences high pressure at the interface. The significant differences in bulk density and flexural strength among the final products of Examples 1, 2, 3, and 4 are mainly due to the different particle sizes of the carbon-graphite matrix formulations used. Generally, finer particle sizes result in higher bulk density and flexural strength in the final product.
[0057] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
[0058] Any aspects of this invention not described in detail are well-known to those skilled in the art.
Claims
1. A method for preparing high-strength, high-density graphite, characterized in that, Includes the following: 1) Matrix preparation: The carbon graphite after one firing and impregnation is used as the matrix, and the carbon graphite matrix green body is formed by isostatic pressing. 2) Mixture preparation: The mixture consists of at least three of the following: yellow sand, metallurgical coke, coke powder, raw coke powder, and paste powder. The mixture must contain at least one of the following: raw coke powder or paste powder. The paste powder is a mixture of coke powder and asphalt, with the asphalt content ranging from 5% to 40% by mass. The volatile matter content of the mixture ranges from 4% to 13% by mass. 3) Molding and wrapping the substrate: Place the rubber sleeve into the mold and smooth it out. Put part of the mixed material from step 2) into the bottom, then put the carbon graphite substrate from step 1) into the rubber sleeve. Continue to add the mixed material to fill the rubber sleeve, so that the carbon graphite substrate is completely wrapped by the mixed material. Seal the rubber sleeve, and after vacuuming, perform isostatic pressing. The maximum pressure of isostatic pressing should be less than the molding pressure of the carbon graphite substrate green body. The pressure of isostatic pressing is 20-130 MPa. 4) Subsequent process: The encapsulated matrix obtained in step 3) is loaded into a furnace and roasted in a ring furnace for 300-480 hours, and then graphitized to obtain high-strength and high-density graphite.
2. The method for preparing high-strength, high-density graphite according to claim 1, characterized in that: In step 3), the thickness of the coating layer formed by the mixture on the surface of the carbon-graphite matrix is 0.2-2 times the corresponding dimension of the carbon-graphite matrix.
3. The method for preparing high-strength, high-density graphite according to claim 1, characterized in that: In step 2), the D50 of the particle size of yellow sand and metallurgical coke particles is 0.5-5mm, and the D50 of the particle size of coke powder, raw coke powder and paste powder is 5-500μm.
4. The method for preparing high-strength, high-density graphite according to claim 1, characterized in that: In step 3), the vacuuming time is 3-10 hours.
5. The method for preparing high-strength, high-density graphite according to claim 1, characterized in that: In step 1), the particle size D50 of the carbon graphite matrix green body is 0.5-5000 μm, and its shape is cuboid or cylindrical.
6. The method for preparing high-strength, high-density graphite according to claim 1, characterized in that: In step 4), the calcination temperature is 800-1200℃; the graphitization temperature is 2500-2900℃, and the holding time is 6-24h.
Citation Information
Patent Citations
Pressurization roasting method for carbon
CN102249212A
Method for preparing binder-free graphite product
CN102060293A
Roasting technology for isostatic pressing formed graphite primary roasting
CN108751182A